Genome-Wide Transcriptional Responses of Marine Nematode Litoditis marina to Hyposaline and Hypersaline Stresses - Xie, Yusu; Zhang, Pengchi; Zhang, Liusuo (Frontiers in Physiology, 2021)
Maintenance of osmotic homeostasis is essential for all organisms, especially for marine animals in the ocean with 30‰ salinity or higher. However, the underlying molecular mechanisms that how marine animals adapt to high salinity environment compared to their terrestrial relatives, remain elusive. Here, we investigated marine animal’s genome-wide transcriptional responses to salinity stresses using an emerging marine nematode model Litoditis marina. We found that the transthyretin-like family genes were significantly increased in both hyposaline and hypersaline conditions, while multiple neurotransmitter receptor and ion transporter genes were down-regulated in both conditions, suggesting the existence of conserved strategies for response to stressful salinity environments in L. marina. Unsaturated fatty acids biosynthesis related genes, neuronal related tubulins and intraflagellar transport genes were specifically up-regulated in hyposaline treated worms, while exhibited the opposite regulation in hypersaline condition. By contrast, cuticle related collagen genes were enriched and up-regulated for hypersaline response, while most of them were remarkably down-regulated in hyposaline condition. Given a wide range of salinity tolerance of the marine nematodes, this study and further genetic analysis of key gene(s) of osmoregulation in L. marina will likely provide important insights into biological evolution and environmental adaptation mechanisms in nematodes and other invertebrate animals in general.